Nilai Indeks Glikemik Sereal Jagung dengan Penambahan Kacang Hijau dan Kacang Merah (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Cereal is an instan food can be consumed as breakfast or as a side dish. The development of corn cereal products is an effort to modify ingredients and diversify local food. The aim of substation addition was to increase the protein and fiber content to reduce the glycemic index value so that it can control blood glucose levels. The study purpose was to describe the glycemic index of mung bean corn cereal and red bean corn cereal. The method was pre-post test control group design. The subjects were 10 students. Subjects were given treatment three times, namely pure glucose, mung bean corn cereal and red bean corn cereal. Each treatment was given a gap of 2 days. Each treatment was checked for blood glucose five times, namely at minute 0 (fasting glucose, the subject had fasted for 8 hours), and after treatment at minutes 30, 60, 90, 120. Determination of the portion of glucose and cereal products was 50 g carbohydrates based on TKPI 2019. The results are the glycemic index of mung bean corn cereal is 28.68 while the glycemic index of red bean corn cereal is 20.32. Both corn cereal products are included in the low category (<50).